2022
DOI: 10.3390/ijerph192416917
|View full text |Cite
|
Sign up to set email alerts
|

HIV Detection and Delayed Diagnosis: A Time Series Analysis in China

Abstract: Background: Insufficient HIV detection and late presentation to antiretroviral therapy (ART) pose significant public health challenges. In China, universal access to HIV testing is available now. Under this background, we aim to analyze the trends of HIV detection and the prevalence of delayed HIV diagnosis (DHD) in order to provide evidence for HIV prevention and treatment in China. Methods: Data of HIV tests in Hangzhou city between 2007 and 2018 were collected from the Chinese National HIV/AIDS Comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This may stem from passive testing-detected individuals displaying inadequate HIV testing awareness and deficient HIV knowledge. In contrast, those identified through VCT exhibit more risk awareness and will voluntarily mitigate risky sexual behavior following the consultation [ 31 , 32 ]. Despite the gradually decreasing HRHB risk among MSM, the high potential for transmission persists, given the extensive population of bisexual individuals who function as a "bridge".…”
Section: Discussionmentioning
confidence: 99%
“…This may stem from passive testing-detected individuals displaying inadequate HIV testing awareness and deficient HIV knowledge. In contrast, those identified through VCT exhibit more risk awareness and will voluntarily mitigate risky sexual behavior following the consultation [ 31 , 32 ]. Despite the gradually decreasing HRHB risk among MSM, the high potential for transmission persists, given the extensive population of bisexual individuals who function as a "bridge".…”
Section: Discussionmentioning
confidence: 99%
“…The high number of chronically infected individuals in Hangzhou has hindered HIV/AIDS control. Sexual transmission has become a major mode of HIV transmission in Zhejiang Province; however, homosexuality remains highly stigmatized and discriminated against in China [ 29 ]. As a result, Chinese MSM tend to hide their identity and engage in sexual behavior in other areas.…”
Section: Discussionmentioning
confidence: 99%
“…A study on partner testing of HIV-infected individuals in Zhejiang showed that nearly 80% of the partners who were successfully tested positive for HIV were newly diagnosed infections [33]. Furthermore, research has shown that HIV patients diagnosed through passive detection have a higher prevalence of delayed HIV diagnosis [34]. In comparison to those diagnosed at voluntary counseling and testing (VCT) clinics, the lower rate of access to HIV-1 molecular transmission networks among HIV-infected individuals diagnosed through VCT may be related to earlier detection of their own diagnosis and delayed detection of the sexual partner who caused their infection.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1,161 newly diagnosed HIV-positive individuals were included in our study from 2019 to 2021. Among them, 93.88% were male, and the median age was 29 years old (with an interquartile range [IQR] of [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The majority of the participants (97.93%) belonged to the Han ethnicity, and 62.45% were unmarried.…”
Section: Basic Characteristics and Subtype Distributionsmentioning
confidence: 99%